Building public trust : - DiPiazza, Samuel A. (John Wiley & Sons, 2002)
Business reporting in a post-apocalypse global marketplace Clearly, now is the time for creating an effective business-reporting model appropriate for the markets of the twenty-first century. Rather than start from scratch after the Enron-Andersen fiasco, two leading consultants from PricewaterhouseCoopers present a plan that supplements the current model, one in which executives, accountants, analysts, investors, regulators, and other stakeholders can truly embrace the spirit of transparency. The Future of Corporate Reporting highlights the best practices for global financial reporting, explaining the concept of "performance auditing," which focuses on the real performance of the business as opposed to technical adherence to GAAS. Eccles and Masterson also discuss the pros and cons of GAAP v. IAS, present new approaches to reforming financial reporting, and outline a twenty-first-century model of accounting that will improve markets and benefit shareholders.